1999
DOI: 10.1007/bf02462094
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged incubation of unhatchable eggs in Red-necked Grebes (Podiceps grisegena)

Abstract: SummaryFrom 1995 to 1998 seven cases of prolonged incubation of unhatchable eggs by Red-necked Grebes (Podiceps grisegena) were observed in south east Poland, all of relatively constant duration (34-36 days). The regular occurrence of prolonged incubation can be attributed to low hatchability rates. It is argued that the failure in assessment of the current egg viability is a by-product of excessive nest attendance as a primary adaptation to irregularities in hatching spreads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Powell et al (1997) attributed the high viability of abandoned eggs to the fact that they were abandoned in early stages and embryos tended to be less sensitive to extreme temperatures at these stages; however, in our study, eggs that were abandoned in all stages of incubation showed signs of viability and development. Abandonment of viable eggs and the prolonged incubation of non‐viable eggs (Kloskowski 1999), suggests that embryo‐adult communication (Ar et al 2004) may not be affecting incubation behavior or nest tenacity in piping plovers. Therefore decreased parental care is likely caused by factors other than loss of egg viability.…”
Section: Discussionmentioning
confidence: 99%
“…Powell et al (1997) attributed the high viability of abandoned eggs to the fact that they were abandoned in early stages and embryos tended to be less sensitive to extreme temperatures at these stages; however, in our study, eggs that were abandoned in all stages of incubation showed signs of viability and development. Abandonment of viable eggs and the prolonged incubation of non‐viable eggs (Kloskowski 1999), suggests that embryo‐adult communication (Ar et al 2004) may not be affecting incubation behavior or nest tenacity in piping plovers. Therefore decreased parental care is likely caused by factors other than loss of egg viability.…”
Section: Discussionmentioning
confidence: 99%
“…1996, Hunt & Evans 1997), particularly in species with a high rate of offspring failure and where an efficient mechanism exists to eliminate excess offspring. Egg and young losses other than rank‐dependent mortality appear to be significant in Red‐necked Grebes (De Smet 1987, Kloskowski 1999). Clutch size affected the probability of late eggs being abandoned; however, it was not associated with the number of chicks fledged.…”
Section: Discussionmentioning
confidence: 99%
“…I recorded nest desertion if the eggs were cold and uncovered and the adults showed no interest in the nest during 1–2 h of subsequent observation. I defined prolonged incubation as an extension in the time of incubation of a dead egg for at least a week over the average egg attendance time of 24 days (Kloskowski 1999). Although Red‐necked Grebes are apparently not able to assess the current viability of eggs, egg desertion was classified only as abandonment of presumably viable eggs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behaviour occurs regularly in the Procellariiformes (e.g. Boersma & Wheelwright 1979, Chaurand & Weimerskirch 1994, Huin 1997 and occasionally in the Podicipediformes (Kloskowski 1999, Nuechterlein & Buitron 2002. It has been linked to intermittent incubation or egg-neglect, as a consequence of long foraging distances (Pefaur 1974, Boersma & Wheelwright 1979 or the avoidance of predation (Nuechterlein & Buitron 2002), respectively.…”
mentioning
confidence: 99%